Tall Structure Seismic Behaviour Analysis with Solid and Coupled Shear Walls - Gunasheela P., (International Journal of Management Studies (IJMS), 2019)
The construction of high rise structures increases due to shortage of land and rapid growth of population. Introduction of advancement in construction materials and structural systems against lateral loads designer will achieve structural efficiency, aesthetic appearance and geometric versatility. Shear walls are structural systems which provide stability to structures from lateral loads. Coupled shear walls are one of the system commonly used in medium and high rise structures to resist lateral loads. When two shear walls are interconnected by beams along their heights then it is called as coupled shear wall. These building systems should not collapse or be induced to severe damage during earthquake actions due to high strength, high ductility, high energy absorption capacity and high shear stiffness to limit lateral deformation. In Coupled shear wall structure, major portion of lateral load is taken by the Coupled shear wall members, when intern releases forces to other members of the structure. This also reduces sectional requirement of the beams and columns in Coupled shear wall building. In the present study, the structural response of conventional, Shear wall and Coupled shear wall with different location investigated to evaluate structural system benefits. A building of G+11 storeys with plan size 23.2m x 17.4m, located in a seismic Zone V is considered and analyzed by ETABS 2016 Software. Nine models, i .e conventional frame structure, Shear wall in different location and Coupled shear wall in different location with same plan area are considered for study. All structural members are analysed as per Indian Standard codes. Comparison of analysis result in terms of Time Period, Storey Shear, Storey displacement Storey Drift, Storey Stiffness of structure is presented. From the analysis results it is observed that, the Coupled shear wall structures along X direction performs better in terms Time Period, Storey Shear, Storey displacement, Storey Drift, Storey Stiffness. Coupled shear wall in intermediate X and Y direction shows more weight difference compared to shear wall.